2021
DOI: 10.1002/pca.3050
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis and identification of dianthrone glycosides in Polygoni Multiflori Caulis based on enrichment of macroporous absorbent resin and UPLC‐Q‐TOF‐MS/MS

Abstract: Introduction Polygoni Multiflori Caulis (PMC) has been used as a traditional Chinese medicine for a long time in China. However, hepatotoxic events of PMC have been reported in recent years, but the potential toxic compounds have remained unclear. Dianthrones as the secondary plant metabolites were revealed to potential hepatotoxicity in a previous study. However, no reports focused on dianthrones in PMC. Objective In the quest for exploring potential hepatotoxic compounds in PMC, the aim of this work was to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Due to its high selectivity and sensitivity, the UPLC-Q-TOF-MS/MS technique is considered an appropriate means to accurately analyze the ingredients of CWT. Recently, this technique has been used to analyze TCM and other natural medicines ( Bo et al, 2021 ; Cheng et al, 2021 ; El-Sabagh et al, 2021 ; Lin et al, 2021 ), revealing details of unknown components that are considered groundbreaking discoveries in the field. In this experiment, the UPLC-Q-TOF-MS/MS technique was adopted to analyze the ingredients of CWT, and the methodology was combined with other network pharmacology techniques used to examine the potential targets and metabolic pathways of CWT ingredients in the treatment of insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high selectivity and sensitivity, the UPLC-Q-TOF-MS/MS technique is considered an appropriate means to accurately analyze the ingredients of CWT. Recently, this technique has been used to analyze TCM and other natural medicines ( Bo et al, 2021 ; Cheng et al, 2021 ; El-Sabagh et al, 2021 ; Lin et al, 2021 ), revealing details of unknown components that are considered groundbreaking discoveries in the field. In this experiment, the UPLC-Q-TOF-MS/MS technique was adopted to analyze the ingredients of CWT, and the methodology was combined with other network pharmacology techniques used to examine the potential targets and metabolic pathways of CWT ingredients in the treatment of insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Polygoni Multiflori Caulis (PMC) is the dried stem of PM, which is also included in ChP (Zhao et al, 2013;Wang et al, 2017;Bo et al, 2021). According to ChP, PMC is used to treat sleeping disorder, rheumatic arthralgia, and skin pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…According to ChP, PMC is used to treat sleeping disorder, rheumatic arthralgia, and skin pruritus. Pharmacological studies have indicated its hypnosis, antidiabetic, and antioxidant effects (Bo et al, 2021). Although PMC has a larger amount of usage in clinical practice than RPM and PMP, fewer cases on liver injury induced by PMC are reported.…”
Section: Introductionmentioning
confidence: 99%